Study on Interaction Between Perylene Derivative and Bovine Serum Albumin - Ma*, Yong-Shan; Wang, Ning; Wu, Jun-Sen; Ren, Hui-Xue; Liu, Lei; Wang, Qi (Asian Journal of Chemistry, 2014)
N,N'-bis(L-glutamic amine)-perylene-3,4,9,10-dicarboxylic diimide (PTCDG) was synthesized and characterized, which is water-soluble and yielded high fluorescent quantum. The interaction between PTCDG and bovine serum albumin (BSA) was investigated with fluorescence and absorbance spectroscopy techniques, as well as the influence of the ion intensity on the interaction. The results showed that infinitesimal bovine serum albumin could decrease the fluorescence intensity of PTCDG and the quenching efficiency was altered with change of bovine serum albumin surface charge. Meanwhile, the fluorescence of bovine serum albumin was quenched by PTCDG and the fluorescence intensity of PTCDG increased. The spectra displayed isoacitinic emission point at 515 nm, demonstrating the existence of the interaction and energy transfer between PTCDG and bovine serum albumin.